Severity of Hypoxic Ischaemic Encephalopathy in Neonates with Birth Asphyxia - Rubina Zulfiqar, Rubina Zulfiqar; Samiya Naeemullah, Samiya Naeemullah (Journal of Rawalpindi Medical College, 2007)
Background: To compare the severity of Hypoxic Ischaemic Encephalopathy (HIE) in neonates with birth asphyxia born in Holy Family Hospital (in-cases), and those born at places other than this hospital (out-cases). Methods: This prospective study was carried out in the neonatal unit of Holy Family Hospital, Rawalpindi, from 1st January 2003 to 30th June 2003. One hundred neonates with birth asphyxia were enrolled of which fifty were in-cases and fifty out-cases. They were selected by simple random sampling. The severity of HIE was staged according to Sarnat criteria and these neonates followed daily till discharge and then on fourteenth day of life. At that time HIE outcome was determined as recovered or improved and worsened or died. Results: According to Sarnat’s criteria, majority of the neonates were in stage II or stage III at the time of admission of which 38 (76%) were in-cases and 48 (96%) out-cases, (p value 0.006). On univariate and multivariate analysis neonates admitted in stage III had treatment failure twenty-four times more than those neonates who were in stage I and II. Conclusion: Severity of HIE is significantly more in out-cases and is detected earlier in hospital settings.